Implementation of Terrorism Criminal Sanctions Methods According to Resolution 2560 - Yaumil Fitri Limonu (Universitas Negeri Gorontalo, 2019)
This study aims to find out the application of methods of sanctions against terrorism crimes according to resolution 2560 and national law. The method used in this study is a type of normative research that uses a legal approach as well as case studies. The results of this study show that the application of the 2560 sanctions method is still based on the previous resolution of resolution 2368 (2017) which asks all Member States to more actively submit a list of requests to the identification committee based on previous resolutions on improving the method of sanctions against terrorism crimes.